Effect of citric acid on the performance of LiFePO4 as a cathode material for lithium batteries - Mat, A.; Sulaiman, K.S.; Arof, Abdul Kariem (Springer Verlag (Germany), 2016)
Lithium iron phosphate (LiFePO4) is a potential cathode material for lithium-ion batteries. This material has been prepared via a sol-gel synthesis method using acetate-based reactants with and without chelating agent. The chelating agent is citric acid. The precursor material obtained on heating the reactants at 500 °C for 4 h has been calcined at different temperatures between 500 and 900 °C for another 4 h to obtain the desired product. The structure and morphology of the calcined materials have been verified using X-ray diffraction (XRD) and scanning electron microscopy (SEM). As the calcination temperature increases, larger crystals with clear polyhedral shape have been observed. The LiFePO4 prepared from acetate-based reactants with citric acid chelating agent and calcined at 700 °C for 4 h is observed to deliver 81 mAh/g specific discharge capacity, when coupled with a Li-anode. On calcining the precursor at 700 °C for 12 h, the specific discharge capacity increases to 133 mAh/g.